Fabrication of Water-Soluble Polythiophene/Poly (sulfonic acid diphenyl aniline)/Polyethylene Oxide Electrospun Nanofibers and Their Antioxidant Activities - Huner, Keziban (WILEY-V C H VERLAG GMBH, 2022)
The fabrication and antioxidant properties of polythiophene/poly(sulfonic acid diphenyl aniline)/polyethylene oxide electrospun nanofibers obtained in this study were brought to the literature for the first time. For this, polythiophene/poly(sulfonic acid diphenyl aniline)/polyethylene oxide (PTh/PSDA/PEO) nanofibers containing 5, 10, 20 and 40 % PTH/PSDA composite by weight were produced by electrospinning method. According to both CUPRAC and ABTS assays, these electrospun nanofibers were found to have antioxidant activity. According to both CUPRAC and ABTS assays, the highest antioxidant activity was obtained from PTh/PSDA/PEO4 electrospun nanofiber containing 40 % PTH/PSDA with values of 244 and 111 mu g TE/mg, respectively. This nanofiber was found to be non-toxic according to the MTT assay and its thermal stability was not much different from that of the PEO nanofiber. PTh/PSDA/PEO electrospun nanofibers were biocompatible, water-soluble nanofibers that were candidates for use in many biological applications with further characterization. These electrospun nanofibers were characterized by FT-IR, UV-Vis., H-1 NMR, XRD and TGA. Surface morphologies were investigated by SEM.
Keywords: antioxidant activity; electrospun nanofiber; polythiophene; poly (sulfonic acid diphenyl aniline); poly (ethylene oxide); BLEND; Chemistry